Correction: Recent developments in photonic, plasmonic and hybrid nanowire waveguides. Issue 12 (7th March 2019) - Kim, Sanggon; Yan, Ruoxue
Abstract : Correction for 'Recent developments in photonic, plasmonic and hybrid nanowire waveguides' by Sanggon Kim et al., J. Mater. Chem. C, 2018, 6, 11795–11816.